What propels the transition? Understanding push-pull-mooring influences on switching from improper E-waste handling to formal recycling - Muhammed Sajid; Myriam Ertz (Cleaner and Responsible Consumption)
This study investigates the factors influencing consumers' intentions to switch from improper handling to e-waste recycling. Utilizing the theoretical framework of Push-Pull-Mooring (PPM) theory, this research adopts a mixed-methods design. Initially, a qualitative study identifies the push, pull, and mooring factors affecting consumers' switching intentions. Subsequently, the second phase of the research develops and quantitatively tests a framework based on these findings using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived environmental risk and climate change-related health risk perception are push factors in this context. Additionally, government initiatives are identified as pull factors, while perceived convenience is a mooring factor. This research significantly enriches the literature on e-waste recycling and offers practical insights for enhancing e-waste recycling initiatives in developing countries. The study’s comprehensive approach provides a robust basis for understanding and promoting better e-waste management practices in similar contexts.